Enhancing electrochemical performance and membrane stability evaluation of carrageenan/polyvinyl alcohol-graphene oxide membrane in passive DEFCs - Zakaria Z.; Kamarudin S.K.; Osman S.H.; Mohamad A.A.; Salehmin M.N.I. (Elsevier B.V., 2024)
A good electrochemical performance of polymer electrolyte membranes (PEMs) is achieving high membrane selectivity, which is a result of low ethanol permeability and high proton conductivity. Reducing the thickness of PEMs is beneficial for high proton conductivity due to the short distance of proton diffusion. Unfortunately, it results in high ethanol permeability. Thus, achieving high membrane selectivity for good electrochemical performance by balancing the requirements of ethanol permeability and proton conductivity is a critical parameter of PEMs. In this paper, the thickness of the carrageenan/polyvinyl alcohol-graphene oxide membrane was varied from 15 ?m 30 ?m to identify the optimum thickness for good electrochemical performance. With a 25 ?m membrane thickness, the highest membrane selectivity was performed at 1.609 104 S s cm?3, and maximum power density in passive direct ethanol fuel cells was achieved at 14.5 mW cm?2, using 2.0 mg cm?2 anode catalyst loading and 2 M ethanol concentration at 70 C, respectively. Furthermore, this membrane has sustained electrochemical performance for 1000 h at 70 C without degrading the membrane stability. 2023 Elsevier B.V.